Automated analysis of mitochondrial dimensions in mesenchymal stem cells: Current methods and future perspectives. Issue 1 (January 2023) - Summer, Sabrina; Kocsis, Agnes; Reihs, Eva Ingeborg; Rothbauer, Mario; Lonhus, Kirill; Stys, Dalibor; Ertl, Peter; Fischer, Michael B.
Abstract: As centre of energy production and key regulators of metabolic and cellular signaling pathways, the integrity of mitochondria is essential for mesenchymal stem cell function in tissue regeneration. Alterations in the size, shape and structural organization of mitochondria are correlated with the physiological state of the cell and its environment and could be used as diagnostic biomarkers. Therefore, high-throughput experimental and computational techniques are crucial to ensure adequate correlations between mitochondrial function and disease phenotypes. The emerge of microfluidic technologies can address the shortcomings of traditional methods to determine mitochondrial dimensions for diagnostic and therapeutic use. This review discusses optical detection methods compatible with microfluidics to measure mitochondrial dynamics and their potential for clinical stem cell research targeting mitochondrial dysfunction.